Insight into the Electrical Double Layer of an Ionic Liquid on Graphene - Jurado, L. Andres (Sci Rep, 2017)
Graphene is a promising next-generation conducting material with the potential to replace traditional electrode materials in supercapacitors. Since energy storage in supercapacitors relies on the electrolyte-electrode interface, here we elucidate the interfacial subnanometer structure of a single component liquid composed solely of cations and anions – an ionic liquid- on electrified graphene. We study the effect of applied potential on the interaction between graphene and a silicon tip in an ionic liquid and describe it within the framework of the Derjaguin-Landau-Verwey-Overbeck (DLVO) theory. The energy is stored in an electrical double layer composed of an extended Stern layer, which consists of multiple ion layers over ~2 nanometers, beyond which a diffuse layer forms to compensate the applied potential on graphene. The electrical double layer significantly responds to the applied potential, and it shows the transition from overscreening to crowding of counterions at the interface at the highest applied potentials. It is proposed that surface charging occurs through the adsorption of the imidazolium cation to unbiased graphene (likely due to π-π interactions) a﻿nd that the surface potential is better compensated when counterion ﻿crowding happens. This study scrutinizes the electrified graphene-ionic liquid interface, with implications not only in the field of energy storage, but also in lubrication.